Bronchoscopic and high-resolution CT scan findings in children with chronic wet cough - Douros, Konstantinos; Alexopoulou, Efthymia; Nicopoulou, Aggeliki; Anthracopoulos, Michael B.; Fretzayas, Andrew M.; Yiallouros, Panayiotis K.; Nicolaidou, Polyxeni; Priftis, Kostas N. (My University, 2011)
Background: Chronic wet cough strongly suggests endobronchial infection, which, if left untreated, may progress to established bronchiectasis. Our aim was to compare the effectiveness of chest high-resolution CT (HRCT) scanning and flexible bronchoscopy (FB) in detecting airway abnormalities in children with chronic wet cough and to explore the association between radiologic and bronchoscopic/BAL findings. Methods: We retrospectively evaluated a selected population of 93 children (0.6-16.4 years) with wet cough for > 6 weeks who were referred to a specialized center and deemed unlikely to have asthma. All patients were submitted to hematologic investigations, chest radiographs (CXRs), HRCT scanning, and FB/BAL. HRCT scans were scored with the Bhalla method, and bronchoscopic findings of bronchitis were grouped into five grades of severity. Results: Positive HRCT scan findings were present in 70 (75.2%) patients (P =.76). A positive correlation was found between Bhalla score and duration of cough (rho = 0.23, P =.028). FB/BAL was superior to HRCT scan in detecting abnormalities (P < .001). The Bhalla score correlated positively with type III (OR, 5.44, 95% CI, 1.92-15.40, P =.001) and type IV (OR, 8.91, 95% CI, 2.53-15.42, P =.001) bronchoscopic lesions, it also correlated positively with the percentage of neutrophils in the BAL (rho = 0.23, P =.036). Conclusions: HRCT scanning detected airway wall thickening and bronchiectasis, and the severity of the findings correlated positively with the length of clinical symptoms and the intensity of neutrophilic inflammation in the airways. However, HRCT scanning was less sensitive than FB/BAL in detecting airway abnormalities. The two modalities should be considered complementary in the evaluation of prolonged wet cough. CHEST 2011, 140(2):317-323
Keywords: Cough; Asthma; Wet cough